Ordinances and Joint Resolutions of the City of San Francisco 220 (1854) - (:unkn) unknown (My University, 1853)
Ordinance No. 498, section 13: Every person, house, or firm engaged in keeping a pistol or rifle shooting gallery, shall pay for a license to carry on the same, the sum of ten dollars per quarter, in addition to the amount of the powder license.
Keywords: SHOOTING RANGES OR GALLERIES